Hubungan Antara Intensitas Penggunaan Media Sosial Dengan Gejala Depresi Pada Mahasiswa FKM UMI (Window of Public Health Journal, 2025)
The high number of adolescents today results in many impacts in mental health issues such as the incidence of depression. Depression is a mood disorder that causes feelings of sadness and loss of interest that occur continuously. The incidence of depression is triggered by the intensity of students using social media. Social media intensity is related to attention, appreciation, duration and frequency. The purpose of the study was to determine the relationship between the intensity of social media use and symptoms of depression in students of the Faculty of Public Health, Muslim Indonesia University. This type of research is with a cross sectional approach in quantitative methods. The population was 448 students with a sampling technique of Proportionate Stratified Random Sampling with a sample size of 82 students. The instrument used a questionnaire in the form of Google Form. Data analysis using univariate and bivariate analysis using the chi-square test. The results showed that there was no relationship between the attention variable in the use of social media with depressive symptoms where the value was obtained (p=0.638) and there was no relationship between the appreciation variable in the use of social media with depressive symptoms where the value was obtained (p=0.582) while the duration variable in the use of social media with depressive symptoms there was a significant relationship where the value was obtained (p=0.000) and the frequency variable in the use of social media with depressive symptoms showed that there was a significant relationship where the value was obtained (p=0.001 α=0.05). The conclusion of the study is that there is a significant relationship between the variables of duration and frequency in the use of social media with symptoms of depression while there is no significant relationship between the variables of attention and appreciation with symptoms of depression in students of the Faculty of Public Health.